Implementasi Pendidikan Karakter Anti Korupsi Di MAN 4 Kediri - Muhamad Faiz Amiruddin; Binti Nur Afifah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Corruption in Indonesia has been seen as an extraordinary crime. It is necessary to make efforts to fortify and eradicate it. The cheapest and most effective way to eradicate corruption is by taking preventive measures, including through anti-corruption education lessons and instilling the values of integrity (non-corrupt behavior) to future generations. Madrasah Nengeri Man 4 Kediri has implemented anti-corruption education quite well, namely by giving teachers training on how to apply 9 anti-corruption characters to students consisting of honest, hard working, disciplined, independent, fair, responsible, caring, simple, and independent.